The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1021/cm100805g
|View full text |Cite
|
Sign up to set email alerts
|

Donor−Acceptor Polymer Electrochromes with Tunable Colors and Performance

Abstract: To demonstrate the effect of donor (D) and acceptor (A) units on the structure-property relationships of electrochromic polymers, design, synthesis, characterization and polymerization of a series of D-A type systems, 1-5, based on thiophene, 3,4-ethylenedioxythiophene, and 3,3didecyl-3,4-dihydro-2H-thieno[3,4-b][1,4]dioxepine as D units and 2,1,3-benzoselenadiazole, 2,1,3benzothiadiazole and 2-decyl-2H-benzo [d][1,2,3]triazole as A units are highlighted. It is found that these units play key roles on the redo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(54 citation statements)
references
References 65 publications
(93 reference statements)
3
50
0
Order By: Relevance
“…To address this issue, an important line of recent research on EC polymers concerns the engineering of the band gaps of conjugated polymers to improve cycle life of the EC devices. A commonly strategy is to adopt donor‐acceptor (D‐A) approach 35–43. The D‐A type conjugated polymers have alternating electron rich and electron deficient groups on their backbones.…”
Section: Electrochromic Materialsmentioning
confidence: 99%
“…To address this issue, an important line of recent research on EC polymers concerns the engineering of the band gaps of conjugated polymers to improve cycle life of the EC devices. A commonly strategy is to adopt donor‐acceptor (D‐A) approach 35–43. The D‐A type conjugated polymers have alternating electron rich and electron deficient groups on their backbones.…”
Section: Electrochromic Materialsmentioning
confidence: 99%
“…Cbz, BN, BS and BSe were synthesized according to procedures from the literature [23]. Syntheses of the polymers (PCBN, PCBS and PCBSe) were achieved by Suzuki reaction between Cbz-donor and BX-acceptors respectively (Figure 1).…”
Section: Results and Discussion 31 Synthesis Of Pcbx Polymersmentioning
confidence: 99%
“…The initial compounds (Cbz, BN, BS and BSe) were prepared and characterized according to the literature [23].…”
Section: Experimental Section 21 Materialsmentioning
confidence: 99%
“…Furthermore, these polymers reflect various hues of blue and green pallets of the Red-Green-Blue color-space in the neutral state. 234 Poly(arylenevinylene) derivatives containing, as an acceptor unit, 2,1,3-benzothiadiazole are good electron transporters with low band gap and broad absorption range. It was shown that the vinyl spacer maintains the electron affinity, reduces the band Downloaded by [Laurentian University] at 08:03 25 November 2014 gap and widens the absorption range.…”
Section: Figure 13mentioning
confidence: 99%